Analysis of the Decision of the Kotabumi District Court Decision Number: (109/PID.SUS/2019/PN) regarding Nursing Personnel Who Perform Operations without Delegation of Authority from Doctors : Analisis Putusan Pengadilan Negeri Kotabumi No: (109/PID.SUS/2019/PN) tentang Tenaga Keperawatan yang Melakukan Operasi tanpa Pelimpahan Wewenang dari Dokter - Fitria, Anis; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the juridical analysis of the decision of the Kotabumi District Court with the number 109/PID. SUS/2019/PN KBU. The research method that the author uses is a normative juridical approach using a case approach or commonly known as a case approuch. The conclusion in this study explains that the decision of the Kotabumi District Court with the number . 109/PID. SUS/2019/PN KBU is appropriate because the delegation of authority from doctors to nurses as described in Article 29 paragraph 1 letter e of the Nursing Law is not merely in writing, but the delegation has been included in the SIP. therefore jumraini was found guilty because he was proven to have violated article 46 paragraph (1) and was subject to administrative sanctions.